The Concept of Knowledge in Islam: An Analytical Study from the Perspective of the Islamic Worldview - Ahmad Akbar Fauzi; Muhammad Wildan Shohib; Mohammad Zaki Azzani; Yassir Hafidh Fitriyan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the concept of knowledge in Islam through the lens of the Islamic worldview, arguing that the issue is crucial in an age where scientific development is often shaped by secular assumptions. Although previous studies have highlighted differences between Islamic and Western epistemologies, they have rarely explored how revelation and reason can be systematically integrated and operationalized within contemporary scientific and educational practices. Accordingly, this study asks: how does the Islamic worldview conceptualize knowledge, and how can this vision inform the development of modern science and society? Using a qualitative, library-based design, the research analyzes classical and contemporary works, journal articles, and conference papers related to epistemology, ontology, and Islam science relations. Data were collected through purposive literature selection and analyzed thematically, moving from conceptual mapping, comparison, and synthesis toward evaluative interpretation. The findings reveal that knowledge in Islam is simultaneously rational, empirical, moral, and spiritual rooted in tawhid and oriented toward human flourishing. The study contributes a more holistic framework for integrating revelation and reason and recommends future work on curriculum design, policy alignment, and applied models linking ethics, spirituality, and scientific practice.